Do scalar implicatures prime? The case of exclusive 'or' - Husband, EM; Patson, N (Cognitive Science Society, 2021)
Understanding language requires comprehenders to understand not only what speakers say, but what speakers might imply. Scalar items (e.g. some, numerals) often invite comprehenders to compute scalar implicatures, pragmatically strengthening the semantic meaning of scalar items by negating their stronger alternatives. Recent priming evidence suggests that scalar implicatures may share underlying mechanisms, priming both within and between implicature types. We report two experiments designed to extend these finding to or, which has an inclusive meaning that can be strengthened to an exclusive meaning, potentially via scalar implicature. Experiment 1 investigated or alongside some and numerals, holding the number of visual symbols constant. Experiment 2 reduced the visual complexity of Experiment 1. Both experiments found robust within-category priming, but failed to fully replicate or extend between-category priming effects. We discuss implications of these results with respect to visual manipulations and the potential fragility of priming across different categories of scalar implicature.